Workshop on Global Agri-Food Systems to 2050: Threats and Opportunities - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2017)
In order to provide strategic guidance to the directions and priorities of the CGIAR - the world’s largest public sector agricultural research system – the Independent Science and Partnership Council (ISPC) is engaging in a set of foresight activities tailored to the specificities of the CGIAR system. In April 2017 the ISPC co-hosted a workshop with the University of Naples on Global Agri-Food Systems to 2050: Threats and Opportunities. The objective of the workshop was to engage expertise outside the CGIAR System for perspectives on major trends and possible disruptions to the global food system to 2050.